Does Entrepreneurial Orientation Influence the Sustainability Performance of Indonesian SMEs? - Fahrul Ismaeni; Fanny Martdianty; Athiyyah Adhikaputri; Rahmadi Triyono (APMBA (Asia Pacific Management and Business Application), 2024)
There is rising awareness regarding the need to incorporate the sustainability concept into business activities worldwide. However, there is rare research concerning implementing 3P's (people, planet, and profit) for Indonesian small and medium-sized enterprises (SMEs), despite SMEs being business players contributing significantly to the Indonesian economy. This research study aims to fill the gap. Specifically, this research aims to analyze the impact of entrepreneurial orientation (EO) on the sustainability performance of Indonesian SMEs. Furthermore, we evaluate the mediating role of knowledge integration capability and sustainability attitude on the relationship between entrepreneurial orientation and SME's sustainability performance. This study surveyed SMEs in Greater Jakarta to collect primary data, and interviewed SMEs who generated support from Indonesia's state-owned enterprises (SOE), such as Wijaya Karya, Jamkrindo, and the Ministry of Cooperatives and SMEs agency body. There were 123 respondents who took part in this research. Structural Equation Modeling (SEM) with Lisrel 8.51 software was used to process the data. The findings suggested that entrepreneurial orientation improved knowledge integration capability, and that knowledge integration capability improved SME's sustainability performance. Meanwhile, we found that entrepreneurial orientation positively affects the SMEs' sustainability attitude, and that the sustainable attitude affects the SMEs' sustainability performance. However, there was insufficient evidence that entrepreneurial orientation directly impacted the sustainability performance of SMEs in Indonesia.